Assessment of Iron Status in Hemoglobin E and b Thalassemia Carriers - Karim, Md Anwarul; Jamal, Chowdhury Yakub; Md Selimuzzaman, -; Miah, MA Mannan (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: About 10-13% people of Bangladesh are carrier of HbE and b- thalassaemia. Many program have been taken by Government and NGOs for supplementation of iron to raise hemoglobin level of children which may not be beneficial or might be harmful to the carriers of this disease. Objectives: of the study was to assess the iron status of Hemoglobin E and b thalassemia carriers thereby to develop iron supplementation strategy for these carriers. Methods: This cross sectional analytic study was on 206 carriers of Hemoglobin E and b thalassemia and 54 healthy controls. Complete blood count with RBC indices, Hemoglobin (Hb) electrophoresis and serum ferritin, serum iron and TIBC were carried out for all subjects following standard protocol. Data were analyzed by Statistical Package for Social Science (SPSS) Version 12. Results: Among 260 subjects 206 were carriers and 54 were control. Number of male was 137 and female was 123 and male to female ratio was 1.1:1. Age of the subjects ranges from 1 year to 59 years with a mean age (±SEM) of 23.07± 0.84 years. Mean age (±SEM) of cases was 22.78 ± 0.971 years and that of control was 24.17 ± 1.63 years. Hematological parameters such as mean (±SEM) Hb concentration, MCV, MCH, and MCHC of carriers were significantly low as compared to the control (p value < 0.01 in all comparison). Mean serum ferritin and iron level in carriers were higher than control however; statistical significance between the values were not found (p value >0.5). Out of 206 carriers 27 (13.1%) cases had IDA and it’s frequency was similar among HbE (14.2%) and thalassemia carriers (12.2%) and prevalence of IDA among the carriers were high (37.5 %) in age group 1-5 years which rises to 52.5% in under nourished children. Conclusion: Carriers of HbE and b thalassemia do have relatively higher iron profile as compared to control but not statistically significant. Iron deficiency anemia is not uncommon in carriers especially in children. So there is no contraindication of iron supplementation to the children in general. DS (Child) H J 2020; 36(1) : 25-33